BAHAUDDIN NAQSHBAND'S VIEWS ON HUMAN DEVELOPMENT (Scientific journal of the Fergana State University, 2024)
In this article, it is emphasized that Bahauddin Naqshband called all people in the society to be a friendly alliance with each other and not to fight against bad people through words, not to hate them, but to realize that he is also a human being, understand his mistakes and help him to take a place among good people.